Perancangan dan Implementasi Smart kWh Meter Berbasis ESP32 untuk Manajemen Energi pada Pelanggan Rumah Tangga 1300 VA - Nursalim Nursalim; wellem F Galla; Silverster Tena; Nixson J. Meok (Jurnal Media Elektro, 2025)
This study aims to design and implement a smart kWh meter system based on ESP32 that is capable of monitoring and controlling electricity consumption in households with a connected power of 1300 VA. The developed system utilizes the ESP32 microcontroller as the main data processor, which is integrated with the PZEM-004T sensor to measure electrical parameters, including voltage, current, power, energy, and power factor. Measurement data is displayed in real-time through the Blynk application, while control and limitation of energy consumption are managed using a Telegram bot service. The system is equipped with a relay to automatically disconnect the load when energy consumption exceeds a predetermined limit. System testing is conducted by comparing the sensor measurement results against the PLN kWh meter as a reference tool. The test results indicate that the developed smart kWh meter system operates effectively and possesses an average current measurement accuracy of above 99% across various types of household loads. Additionally, the load control and notification system based on Telegram functions reliably in limiting electricity consumption. Therefore, this system can serve as an effective solution to assist household users in monitoring and controlling electricity consumption more efficiently.